PELAKSANAAN PEMBELAJARAN DI STAI RAKHA SEBELUM, SEMASA DAN SESUDAH PANDEMI COVID-19 - Syaiful Ahmadi; Syahrani (CV. ADIBA AISHA AMIRA, 2023)
In the application of online learning, which tends to be in the form of giving assignments through applications. Fortunately, learning activities in several schools in Indonesia, most of them can run well. However, there are still shortcomings due to constraints, namely the limited ability to adapt and master information technology by teachers and students, inadequate facilities and infrastructure, limited internet access. Exploring the problems faced in the implementation of learning activities with the aim of knowing 1) how to implement learning, and 2) what are the obstacles in the implementation of learning. The research was conducted by means of a literature review to review previous research. Based on the results of data analysis, it can be concluded several things including: 1) online learning is the best effort that can be done in order to break the chain of the spread of the Covid-19 virus, especially in the field of education, 2) Online learning can be done using various internet-based applications such as WhatsApp Group, Zoom Cloud Meeting, Google Classroom, Google Form, e-mail and so on, 3) obstacles faced in carrying out online learning activities including the lack of supporting facilities and infrastructure, unstable internet services, requiring a fairly large quota, unequal distribution of resources humans who master technology well, communication in the learning process does not go well, limited learning methods applied in learning activities, and lack of supervision of student development. In addition, this study also intends to describe the changes in the face-to-face learning process after being online during the Covid-19 pandemic.